Translanguaging and the body. Issue 3 (3rd July 2017) - Blackledge, Adrian; Creese, Angela
ABSTRACT: This article reports communicative interactions with a focus on the body as a dimension of the semiotic repertoire. The research context is a four-year, multi-site linguistic ethnography which investigates how people communicate in superdiverse cities in the UK. In the setting of a butcher's stall in a city market we consider three interactions at a particular market stall between butchers and their customers. In the first, gesture is deployed as a resource by both an English butcher's assistant and his customer. In the second, we examine the body as a resource in the semiotic repertoire of a Chinese butcher as he negotiates a faux haggling interaction with East European customers. In the third example, also recorded as field notes, a Chinese woman employs a 'Chinese' gesture to represent the number of pieces of offal she wishes to purchase from an English butcher's assistant. Each of the examples was recorded during an extended period of ethnographic field work in Birmingham Bull Ring market. Through detailed analysis of these interactions we argue that when people's biographical and linguistic histories barely overlap, they translanguage through the deployment of wide-ranging semiotic repertoires.